IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI MA AL MUHAMMAD CEPU - Sariman Sariman (Pascasarjana IAIN Sorong, 2021)
An important role in academic supervision at MA Al Muhmmad Cepu is an effort to improve the quality of education at madrasas, researchers use exploratory case study research methods, through observation, interviews, and document studies on the implementation of supervision at MA Al Muhammad Cepu, the data is analyzed descriptively. The results of the study are; 1. In carrying out supervision, the madrasah principal makes plans, schedules, and instruments, and implements the principles of supervision. 2. The implementation of educational supervision in improving the quality of education at MA Al Muhammad Cepu encounters various problems the kinds of problems include Human Resource Problems, Funding Problems, Facilities and Infrastructure, and the Commitment Problem of the Ministry of Religion